Perbaikan Kerusakan Geser Kolom Beton Bertulang Penampang Persegi Dengan Carbon Fiber Jacket - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
Shear failure of column is the most dangerous one because the structure will collapse in brittle manner. Therefore a shear-damaged column must be repaired with a correct method. This research employed carbon fiber jacket material to repair and strengthen column. The objectives of this research are to know the shear strength, lateral load capacity, stiffness, drift ratio and modes of failure of the intact as well as retrofitted columns. This research used 6 specimens consisted of 2 repaired columns, 2 strengthened columns and 2 reference columns. The columns had rectangular cross sections of 160 x 160 mm, 500 mm high and had 8012 longitudinal reinforcements with 04-160 tie, except the reference columns had 6022 and 2012 longitudinal reinforcements. Three specimens were tested subjected to cyclic lateral loading and constant axial load of 10.5 T until maximum lateral load was reached. The concrete cover of the damaged columns was peeled off and changed with new concrete cover then were wrapped with carbon fiber jacket and were retested. The other specimens were strengthened with carbon fiber jacket and were tested with the same manner as the intact columns. Results of the tests showed that modes of failure were changed from shear failure to flexural failure after retrofitting. The lateral load capacity of repaired and strengthened columns increased 54,021 % and 75,566 %, respectively, relatively to the intact columns. The shear strength of repaired column increased 49,290 % relatively to the intact column and the shear strength of strengthened column was higher than the predicted shear strength. The drift ratio of repaired columns was 1.76 times greater than the intact columns and the drift ratio of strengthened columns was 1.17 times greater than the intact columns. At the beginning of the test the stiffness of repaired columns was 1.6 times greater than the intact columns and the stiffness of strengthened columns was 2.54 times greater than the intact columns.